Optimization of Digital Applications for Creative Content Creation in Digital Marketing as A Smart Village Development - Aida Fitrianah Zen (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
The advancement of digital technology offers villages opportunities to adopt the Smart Village concept through digital marketing strategies. This study examines the optimization of digital applications for creating creative content to enhance the village's attractiveness and visibility. The method employed is Community-Based Participatory Research (CBPR), with a case study conducted in a village implementing digital marketing. The findings indicate that applications such as Canva, CapCut, and Shopee can improve content quality, expand promotional reach, and attract tourists and investors. However, challenges such as digital literacy and internet access remain significant obstacles. The proposed solutions include training and mentoring programs for village communities to help them use technology optimally. Therefore, optimizing digital applications in creative content creation can serve as an innovative strategy to strengthen the Smart Village ecosystem and enhance village competitiveness in the digital era.